A study on personal hygiene and sanitary practices in a rural village of Mornag District of Nepal - Karn, Rajiv Ranjan; Bhandari, Buna; Jha, Nilambar (Journal of Nobel Medical College, 2012)
Background: Inadequate sanitation has direct effect on health of individual, family, communities and nation as a whole. Objective: To assess the personal hygiene and sanitary condition of the Katahari Village Development Committee (VDC). Methods: The cross sectional study was done in Katahari VDC of Morang district. A total of 80 households were randomly selected from two wards of VDC. The data were collected by interview method using interview schedule. Data were entered in Excel sheet and analyzed on SPSS program. Results: Many respondents (61%) were unable to read and write, 33% involved in private job in various factory. Knowledge of sanitation was high (90%) but only 65% of them were using soap water for hand washing. Sixty percent had no toilet facilities. There was significant association between education and toilet facilities among community people. Land holding and type of family had no significant association with toilet facilities. Conclusion: The knowledge regarding sanitation was high among community people but very poor in practice.DOI: http://dx.doi.org/10.3126/jonmc.v1i2.7298 Journal of Nobel Medical College (2012), Vol.1 No.2 p.39-44